Long-term survival after on-pump coronary artery bypass grafting in patients with coronary artery disease in Taiwan - Chia-Chun Hung; Chung-Yi Chang; Ming-Chon Hsiung; Jeng Wei (Aging and Health Research, 2023)
The study analyzed the long-term survival of 1,482 eligible patients with coronary artery disease who received on-pump coronary artery bypass grafting (ONCAB) between 1997 and 2003 in Taiwan. The cumulative all-cause death rate over 23 years was 21.9%, while the cumulative cardiovascular-specific death (CVD) rate was 2.09%. Patients aged ≥ 70 years had a significantly higher incidence rate ratio (IRR) (IRR, 2.183, 95% confidence interval [CI], 1.742–2.731), but the lower cumulative incidence rate ratio (CIRR) (CIRR, 0.634, 95% CI, 0.524–0.767) for all-cause deaths than those aged < 70 years. There was no significant difference for IRR and CIRR of CVD between 2 groups. Overall survival was influenced by hypertension (hazard ratio [HR], 1.412, 95% CI, 1.104–1.806), dyslipidemia (HR, 1.890, 95% CI, 1.506–2.372), and previous stroke (HR, 0.525, 95% CI, 0.391–0.705) in all patients. Our results suggest that ONCAB may be a viable option for older patients.